Asymptotic stability of general linear dynamical networks under distributed relative-state feedback control. Issue 15 (October 2022) - Peng, Shanshan; Zhang, Jinxing; Zhu, Jiandong; Lu, Jianquan; Li, Xiaodi
Abstract: This paper investigates general linear dynamical networks (GLDNs), distributed relative-state feedback control, and pinning control. For symmetric GLDNs under distributed relative-state feedback control, some necessary and sufficient conditions for asymptotic stability are proposed. While for the asymmetric case, some sufficient conditions are derived. If the obtained stability conditions are not satisfied, one can design some pinning controllers to asymptotically stabilize the GLDNs. Compared with the existing results, the considered dynamical network model is more general, and the obtained theoretical results are novel.